1989
DOI: 10.1029/jd094id13p16405
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐year continuous record on the influence of daytime, season, and fertilizer treatment on methane emission rates from an Italian rice paddy

Abstract: CH4 emission rates have been measured in an Italian rice paddy between 1984 and 1986, covering three vegetation periods. For these measurements a fully automated, computerized sampling and analyzing system was developed which allowed the simultaneous determination of CH4 emission rates at 16 different field plots. CH4 emission rates showed strong diurnal and seasonal variations. Diurnal changes correlated with changes in soil temperature. During the season, CH4 emission rates showed a first maximum in May–June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
263
4
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 558 publications
(293 citation statements)
references
References 28 publications
18
263
4
3
Order By: Relevance
“…2. Schütz et al (1989) reported that application of rice straw at 5 t/ha and 12 t/ha increased CH4 rates by factors of 2.0 and 2.4, respectively, compared with no addition of straw.…”
Section: Relationship Between Water and Straw Management Practices Onmentioning
confidence: 99%
See 2 more Smart Citations
“…2. Schütz et al (1989) reported that application of rice straw at 5 t/ha and 12 t/ha increased CH4 rates by factors of 2.0 and 2.4, respectively, compared with no addition of straw.…”
Section: Relationship Between Water and Straw Management Practices Onmentioning
confidence: 99%
“…Average values for each straw incorporation rate were used. The selection of this model was based on the literature, where CH4 emissions have been reported to increase with straw addition until certain value where no further increase in emissions occurs with further addition of straw (Schütz et al, 1989;Kludze and DeLaune, 1995). As a result, the regression equation indicated in Eq 1 was obtained:…”
Section: Relationship Between Water and Straw Management Practices Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the decomposition rate of rice straw (Shiga et al 1985;Watanabe et al 1993) and the effects of its application on methane flux (Schutz et al 1989;Yagi and Minami 1990;Watanabe et al 1998) and nitrogen cycling (e.g. nitrogen fixation, immobilization, and mineralization of nitrogen; Yoneyama et al 1977;Yoneyama and Yoshida 1977a, b, c;Roger and Watanabe 1986) in paddy fields have been studied in detail, the microorganisms responsible for rice straw decomposition in paddy fields have not been well documented.…”
mentioning
confidence: 99%
“…The metabolism of these different microbial communities completes the degradation of organic carbon from large molecules to the most reduced status like methane (Chidthaisong and Watanabe 1997;Hou et al 2000;Le Mer and Roger 2001). The other two procedures that are also included in the emissions of methane from soil to atmosphere (Schu¨tz et al 1989) are: reoxidation and transportation. Both production and oxidation of methane are closely related to the populations and activities of soil microbial communities.…”
Section: Introductionmentioning
confidence: 99%